Arsenic contamination in the deep tube wells of Kathmandu Valley, Nepal (Nepal Journal of Environmental Science, 2013)
A study was conducted at 13 different areas of Kathmandu Valley to know the status of arsenic in deep tube wells in post monsoon and winter in 2009 and 2010. The depth of the deep tube wells ranged from 75 m to 304 m. The study was also carried out to know the correlations between depths of the deep tube wells and arsenic concentration. The collected samples were analyzed as per standard method using spectrophotometer. The correlations of arsenic concentration in different season (post monsoon and winter) were also studied. 92.31% of deep tube wells in post monsoon and winter exceeded permissible values of World Health Organization guideline value 0.01 mg/L for drinking water but 38.46% deep tube wells in post monsoon and 46.15% of deep tube wells in winter exceeded permissible values of Nepal Drinking Water Standard of 0.05 mg/L. There was strong positive correlation in arsenic concentration between post monsoon and winter(r=0.94, p